La danza afroecuatoriana y el proceso de enculturación de la niñez a través del baile tradicional la caderona en el cantón Esmeraldas, provincia de Esmeraldas, 2023 - Góngora Ramos, Rayshel Lilibeth (2023)
The Afro-Esmeraldeña dance is recognized for telling scenically the traditions and stories of ancient events such as: daily, spiritual, sentimental, and even governmental aspects of Afro-Ecuadorians. The enculturation of this culture has been affected mainly by globalization and the distractions it generates. The entertainment in social networks and the acculturation of foreign social behaviors cause a low interest in learning Afro- Esmeraldeña culture. The research aimed to determine the importance of Afro-Ecuadorian dance and the process of enculturation of children through the traditional dance "la caderona" in the Esmeraldas canton, Esmeraldas province. On the other hand, the methodology implemented has a mixed approach. Therefore, quantitative results were obtained through the application of a survey for the collection of statistical data; contextualized knowledge was obtained through the creation and execution of a semi-structured interview, giving us qualitative data. These techniques allowed us to determine the level of cultural knowledge and interest in learning about their culture through dance and the state of enculturation, and the development of local culture. Correct cultural management will allow children and young people to have a successful enculturation process, resulting in cultural empowerment of the population. Complementing this, a proposal was made in the form of a workshop with cultural and artistic character in order to initiate a process of enculturation about the Afro- Esmeraldeña culture in children through the traditional dance of the caderona.